Land Capital Management in North Eastern States - Suraj Bhan, (Journal of Soil and Water Conservation, 2022)
The North Eastern States of India comprising, Arunachal Pradesh, Assam, Meghalaya, Manipur, Mizoram, Tripura, Nagaland and Sikkim, and cover about 8 percent of the total geographical area of the country. The hilly region is bounded by Bhutan and Tibet in the north, Burma (Myanmar)in the east and Bangladesh in the south and west. The region is characterized by difficult terrain and wide variations in slope, altitude, land tenure system and cultivation practices. The cropping intensity of the region as whole is relatively low, although it is higher for Tripura (165%) and Assam (145%). The agricultural production system in the region is mostly rainfed, monocropped and at subsistence level. Majority of the population is dependent on agriculture, horticulture and allied land based activities.The huge loss of topsoil due to high intense rainfall, surface runoff, deforestation and shifting cultivation is the cause of large scale soil degradation is a major problem of concern. Hence, for sustainable agricultural production it is essential to manage these factors using location specific measures to conserve, utilize and manage the natural resources of land & water.